Endocytosis of the thrombopoietin receptor Mpl regulates megakaryocyte and erythroid maturation in mice - Eaton, Nathan; Boyd, Emily K.; Biswas, Ratnashree; Lee-Sundlov, Melissa M.; Dlugi, Theresa A.; Ramsey, Haley E.; Zheng, Shikan; Burns, Robert T.; Sola-Visner, Martha C.; Hoffmeister, Karin M.; Falet, Hervé (Frontiers in Oncology, 2022)
Dnm2fl/fl Pf4-Cre (Dnm2Plt–/–) mice lacking the endocytic GTPase dynamin 2 (DNM2) in platelets and megakaryocytes (MKs) develop hallmarks of myelofibrosis. At the cellular level, the tyrosine kinase JAK2 is constitutively active but decreased in expression in Dnm2Plt–/– platelets. Additionally, Dnm2Plt–/– platelets cannot endocytose the thrombopoietin (TPO) receptor Mpl, leading to elevated circulating TPO levels. Here, we assessed whether the hyperproliferative phenotype of Dnm2Plt–/– mice was due to JAK2 constitutive activation or elevated circulating TPO levels. In unstimulated Dnm2Plt–/– platelets, STAT3 and to a lower extent STAT5 were phosphorylated, but their phosphorylation was slowed and diminished upon TPO stimulation. We further crossed Dnm2Plt–/– mice in the Mpl–/– background to generate Mpl–/– Dnm2Plt–/– mice lacking Mpl ubiquitously and DNM2 in platelets and MKs. Mpl–/– Dnm2Plt–/– platelets had severely reduced JAK2 and STAT3 but normal STAT5 expression. Mpl–/– Dnm2Plt–/– mice had severely reduced bone marrow MK and hematopoietic stem and progenitor cell numbers. Additionally, Mpl–/– Dnm2Plt–/– mice had severe erythroblast maturation defects, decreased expression of hemoglobin and heme homeostasis genes, and increased expression of ribosome biogenesis and protein translation genes, and developed anemia with grossly elevated plasma erythropoietin levels, leading to early fatality by postnatal day 25. Mpl–/– Dnm2Plt+/+ mice had impaired EB development at three weeks of age, which normalized with adulthood. Together, the data shows that DNM2-dependent Mpl-mediated endocytosis in platelets and MKs is required for steady-state hematopoiesis and provides novel insights into a developmentally controlled role for Mpl in normal erythropoiesis, regulating hemoglobin and heme production.